WAQF LAND’S UTILIZATION IN FULFILLING THE WELFARE OF THE WEST SUMATRA COMMUNITY - Onny Medaline; Siti Nurhayati; Irma Fatmawati (Universitas Syiah Kuala, 2022)
In Indonesia, waqf (endowment) is predominantly still administered conventionally. This research aims to examine the various models of waqf land utilization methods in West Sumatra, as well as their benefits and drawbacks. This is legal doctrinal research. The necessary materials for this study are collected through library research. The research demonstrates that financing is required to sustain the operation of the waqf asset itself, which can result in the asset's displacement due to a lack of maintenance expenditures. Many institutions have acted as locations for the diffusion of information and culture and have offered space for scholars, jurists, and culturalists to develop their competence. In addition, buildings of worship, school infrastructure, other social waqf, burial grounds, and Islamic boarding school education dominate the utilization of waqf land in West Sumatra. More economically empowering technologies ought to be incorporated into the development of waqf management models